The social and economic dimensions of drug abuse A field study in Al-Qadisiyah Governorate - Nasseer.Muhsin ALftlawi, Asst.Prof. (lark, 2023)
Research on the topic of drugs is an important goal and a basic requirement at the present time. Many researchers have studied and analyzed it, due to its importance and its connection to aspects of the social life of individuals. The practices that affect the security and stability of society remain at the forefront of the activities that researchers are concerned with in order to maintain the stability and security of these societies. We found out from the research that the encouragement of the respondents to addiction and drug abuse was due to bad friends, as the percentage of respondents who were encouraged by their friends to use was (75%). As it turned out through the field study, narcotic pills are the most popular and widespread among drug users, with a rate of (73.3%)